PENGEMBANGAN SOAL STATISTIKA UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA - Azzahro Nurul Furqoni; Yuriska Destania (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
This research aimed to produce a product in the form of problem-connections of students mathematical was valid and practical (legible). This method of research was research and development. The research was conducted in Bengkulu City with the research subject of 6 students of grade VIII junior high school students and was carried out in May-June 2020. The method of data collection in development was carried out using Tessmer’s, which consists of preliminary, self-evaluation, expert review, and one-to-one. In the preliminary, two stages must be passed, namely preparation from completion. Was analyzing the curriculum, students, and material. Then, the completing the results of the students, curriculum evaluation, and the material was used as a reference for designing the mathematical connection ability, from the solution it produces 20 prototypes which are then assessed and fixed on self-evaluation. Of the 20 prototypes, these items will go through the validation stage (expert review) after 3 validation. Then, obtained 14 valid prototype items based on quantitative and qualitative analysis and test on 6 students to see the practicality or readability of items (one-to-one). The one-to-one stage was carried out to get comments on each question item to be analyzed qualitatively and quantitatively. Based on the qualitative comments, most of the provided students already understand the problem (legible) according to data, the average preceding data (legible) was recorded in the description of the pre-emptive questions at intervals of 4 ≤ RPproduc ≤ 5.